An opportunistic observational study of hospital switchboard hold messages, hold music and time spent waiting - Jordan P. Skittrall; Mary D. Fortune (Future Healthcare Journal)
Numerous callers contact hospital switchboards, many repeatedly. Recorded switchboard messages have broad reach. We sampled outgoing calls from our regional infectious diseases service to other hospital switchboards over a 3-month period. Wait times varied substantially. Two calls were cut off unanswered. Recorded messages commonly covered infection control precautions for visitors, visiting rules, and guidance regarding calling for medical advice. At least one message was out of date. Another advised unwell people not to visit the hospital. We followed up our sample with freedom of information requests, focusing on call volume data and policies regarding switchboard systems and messaging. Many policies were informal. Overall, the user experience varied substantially between hospitals. Messaging policies appeared to have little regard to messages’ relevance, utility and impact. Calling a hospital switchboard is a common, non-biomedical task that would benefit from substantial effort to establish and promote best practice.